Symposium 6: Design for problem and project based learning in a networked society: Symposium Introduction - Dirckinck-Holmfeld, Lone; Nielsen, Jørgen Lerche; Danielsen, Oluf; Sorensen, Elsebeth K.; Nielsen, Janni; Levinsen, Karin; Sørensen, Birgitte Holm (Proceedings of the International Conference on Networked Learning, 2010)
The networked society is challenging the localisation-based organisation of learning and education, especially for professional masters. The professionals need and want to be able to participate in continuing education and life long learning throughout life, however they don’t have to or want to move to university cities in order to pursue a master as well as they want to integrate the study with work based experiences and challenges. Therefore, there is a need to explore and develop new ways of organising educational programmes at masters level, which respond to the needs of the learner, utilize the opportunities of new ways of organising research based teaching and learning at the highest level. The solution is to design for research based learning organised as networked learning. Doing so offers access to a dynamic and flexible learning environment for students as well as professors. MIL (Master in ICT and Learning) is a masters programme organised as a networked learning environment for professionals and professors. MIL is in 2010 celebrating 10 years of birthday. More than 300 masters have graduated, most of them playing an active role in the transformation of the Danish educational system integrating new learning approaches supported by ICT. MIL as an institution in itself is a network, based in collaboration among leading research centres within five Danish universities on different core aspects of ICT and learning. This Symposium gives us an opportunity to reflect on selected issues and practices within MIL. We have selected four issues to explore, reflect and discuss more deeply: • Overall design of a networked learning master environment for professionals • The role of the supervisor and the facilitator • Engaging for digital democratic dialogues • Engaging for productive and producing aspects The overall theoretical approach is based in socio-cultural learning and cognition, and the methodological approach is practice based research. Symposia participants and paper abstracts Design of a Networked Learning Master Environment for Professionals – using the approach of problem based learning to establish a community of practice The paper is presenting the overall learning design of MIL (Master in ICT and Learning). The learning design is integrating a number of principles: 1. Principles of problem and project based learning 2. Networked learning / learning in communities of practice. The paper will discuss how these principles interact productively in the design of a networked learning environment for professionals. Problem-oriented Project Studies – the role of the teacher as supervising / facilitating the study group in its learning processes The paper focuses on the challenges related to the role of the supervisor and the facilitator within problem- and project based networked learning. The facilitator role is viewed in the span of the therapist, the teacher /the expert and the facilitator. The paper is based on reflections on the experiences gained from many years of problem – and project based teaching and learning practices. The paper focus on the practice within Master in ICT and Learning (MIL), which is a primarily collaborative networked learning environment for professionals , which calls for a supervisor /facilitator, which is flexible and able to reflect the complexity role of the supervisor. The theoretical inspirations for the different roles are found in Habermas’s concepts and discussions of communicative actions and strategic communication. Exploring the Digital Democratic Dialogue in Networked Learning Environments. The paper is exploring the digital democratic dialogue in networked learning environments. The paper is going to take point of view in the dialogical practice within MIL (Master in ICT and Learning), and the learning design developed through the last 10 years. Theoretically, the paper will among others draw on Wittgensteins perspective on ‘language games’. A Theoretical Design for Learning Model addressing the Networked Society The paper address that the transition from the industrial to the networked society produces contradictions that challenges the educational system and force it to adapt to new conditions. In a Danish virtual Master in Information and Communication Technologies and Learning (MIL) these contradictions appear as a field of tension between time resources and the demand for educational quality. The aim is to provide a scaffold that ensures students´ acquisition of the subject matter within a time limit and at a learning quality that support their deep learning process during a subsequent period of on-line study work.